2022
DOI: 10.1371/journal.pone.0272565
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of thermoregulation of different pine organs in early spring and estimation of heat reward for the western conifer seed bug (Leptoglossus occidentalis) on male cones

Abstract: The western conifer seed bug (WCSB, Leptoglossus occidentalis) is a pest of many pine species and is invasive worldwide. WCSB directly and indirectly deteriorates pine nut production by sucking seeds from cones. Currently, researchers think that WCSBs search for food by a combination of cues from visible light, infrared radiation, and chemicals such as monoterpenes. Some research revealed that WCSBs prefer larger cones, and it was thought that WCSBs suck seeds from and obtain more heat on larger cones. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
0
0
0
Order By: Relevance
“…Furthermore, higher temperatures lead to an increased release of volatile compounds like monoterpenes. Therefore, male owers, with their high re ectance, high temperature, and high concentration of volatile compounds, may be more appealing to L. occidentalis (Kitajima et al, 2022). Previous research has shown that rst-stage nymphs feed on male owers during the spring season (Schaefer and Panizzi, 2000).…”
Section: Slope and Germinationmentioning
confidence: 99%
“…Furthermore, higher temperatures lead to an increased release of volatile compounds like monoterpenes. Therefore, male owers, with their high re ectance, high temperature, and high concentration of volatile compounds, may be more appealing to L. occidentalis (Kitajima et al, 2022). Previous research has shown that rst-stage nymphs feed on male owers during the spring season (Schaefer and Panizzi, 2000).…”
Section: Slope and Germinationmentioning
confidence: 99%